A DIFFERENCE ON THE EFFECTIVENESS OF ENDORPHIN MASSAGE WITH WARM COMPRESS THERAPY TO DECREASE MOTHER’S BACK PAIN DURING THIRD TRIMESTER OF PREGNANCY AT ALL PUBLIC HEALTH CENTER IN MATARAM - Baiq Eka Putri Saudia; Oky Nila Kencana Sari (poltekkes kemenkes mataram, 2018)
Abstract: Pregnancy is the natural and normal process. Pregnant women get common changes that occur both physically and physiologically. Those changes cause them discomfortort and one of them is back pain. It can be solved by non-pharmacological therapy which is done by doing some activities such as distraction technique, self hypnosis, reducing the pain perception, massaging treatments, relaxing in a hot bath and heat or cold therapy. This research intended to investigate the effect between Endorphin Massage and warm compress therapy to reduce the back pain during the third trimester of pregnancy. This research was a quasi experimental research with two group pre test and post test design in which this experiment was done in two different groups. The sample utilized pusposive sampling technique and conducted at all public health center or puskesmas in Mataram during July to October 2017. The sample consisted of 30 pregnant mothers with third trimester of pregnancy who detected with the back pain through Numerical Rating Scale (NRS). This scale was done before and after they got Endorphine Massage and warm compress for 20 minutes in five days. Afterward, the data was analyzed by using test statistic of independent t test. The result found that mean score before and after the Endorphin Massage was 1.933 while the mean score before and after warm compress was 0.733. Those results indicated that Endorphin Massage was more effective than to reduce the back pain during the third trimester of pregnancy. Endorphine Massage was also used as the alternatif therapy of non-pharmacological to solve the back pain. Therefore all the midwives can apply Endorphine Massage through the midwifery service to the pregnant mothers in which it can help them to solve the back pain problems during the third trimester of pregnancy.